Tumour necrosis factor induces phosphorylation primarily of the nitric-oxide-responsive form of glyoxalase I - deHemptinne, Virginie (Portland Press Ltd., 2007)
We have previously shown that TNF (tumour necrosis factor) induces phosphorylation of GLO1 (glyoxalase I), which is required for cell death in L929 cells. In the present paper, we show that the TNF-induced phosphorylation of GLO1 occurs primarily on the NO (nitric oxide)-responsive form of GLO1. In addition, analysis of several cysteine mutants of GLO1 indicated that Cys-138, in combination with either Cys-18 or Cys-19, is a crucial target residue for the NO-mediated modification of GLO1. Furthermore, the NO-donor GSNO (S-nitrosogluthathione) induces NO-mediated modification of GLO1 and enhances the TNF-induced phosphorylation of this NO-responsive form. GSNO also strongly promotes TNF-induced cell death. By the use of pharmacological inhibition of iNOS (inducible NO synthase) and overexpression of mutants of GLO1 that are deficient for the NO-mediated modification, we have shown that the NO-mediated modification of GLO1 is not a requirement for TNF-induced phosphorylation or TNF-induced cell death respectively. In summary, these data suggest that the TNF-induced phosphorylation of GLO1 is the dominant factor for cell death.